Two Cases of Post-Traumatic Mucormycosis due to Mucor circinelloides: Salvage Therapy with a Combination of Adjunctive Therapies. (4th May 2022) - De Paepe, A.; Dams, K.; Robert, D.; Jacobs, R.; Ten Kate, G. L.; Van Ierssel, S.; Jansens, H.; Lammens, M.; Van Beeck, A.; Jorens, P. G.
Abstract : Mucormycosis is a rare, emerging angioinvasive infection caused by ubiquitous filamentous fungi. In recent decades, an increase in cutaneous or post-traumatic mucormycosis has been reported. We describe two cases of post-traumatic wound infections with Mucor circinelloides, a mucor species only rarely reported as a cause of post-traumatic mucormycosis. Often considered lethal, management required a combination of medical and surgical therapies to achieve a favorable outcome in both cases.